TANGGUNG JAWAB PPAT ATAS BEA PEROLEHAN HAK ATAS TANAH DAN BANGUNAN (BPHTB) PADA AKTA JUAL BELI TANAH DAN BANGUNAN DI KOTA MEDAN - Tania Mayshara Limbong; Ayu Trisna Dewi; Rina Melati Sitompul (Law Jurnal, 2022)
ABSTRACTPPAT in making the deed is to ensure that the payment of BPHTB the debt has been paid by the taxpayer. For this reason, it is necessary to study the role of PPAT in the imposition of BPHTB in the transfer of land rights and building, the legal consequences of the imposition of BPHTB in the deed of sale and purchase of land and buildings and the mechanism for imposing BPHTB in the deed of sale and purchase. Type The research used in writing this thesis is juridical normative empirical, which is descriptive analysis. The data collection techniques used used is literature study and field research. The role of PPAT in The imposition of BPHTB in the Transfer of Land and Building Rights, namely convey the necessary information related to the imposition process BPHTB in the imposition of BPHTB tax on the transfer of land rights and building. The legal consequences of the imposition of BPHTB in the Deed of Sale and Purchase of Land and The building, namely the Sale and Purchase Deed, cannot be carried out before the BPHTB is signed the sale and purchase transfer transaction has not been paid by the taxpayer, which also result in legal certainty in the transition. In addition there are The sanctions imposed by Article 91 paragraph (1) are in the form of paying fines 7,500,000.00 (seven million five hundred thousand rupiah) for each commit a violation if the signing of the Sale and Purchase Deed is done before PPAT before the parties pay the BPHTB tax. Imposition mechanism BPHTB in the Deed of Sale and Purchase, namely preparing complete documents and data tax object, the taxpayer fills in the information on the tax object and the value of the BPHTB payable into the Tax Deposit Form (SSPD) BPHTB, then calculate the value of BPHTB payable. Next is the Taxpayer and PPAT/Notary sign the SSPD form. The payment process is carried out when the documents SSPD BPHTB which is verified as complete and declared correct. Then payment is made through the beneficiary treasurer or through a bank and must tax receipt of proof of deposit/SSPD BPHTB as proof of payment of BPHTBlegal debt.Keywords: PPAT, Imposition of BPHTB, Deed of Sale and Purchase